1993
DOI: 10.1055/s-2007-1021168
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Type and Structure of Complex Carbohydrates Response to Physical Exercise

Abstract: To examine the level of oxidation between different carbohydrate foodstuffs ingested one hour before exercise, three experiments were conducted in men. They performed a series of exercise tests of two hours duration at 60% VO2max preceded in experiment I by ingestion of one of five isocaloric (836 kJ) successive meals of bread, potatoes, rice, spaghetti, or glucose; in experiment II, by either spaghetti or glucose, both naturally 13C enriched; in experiment III, by one of four 13C labelled meals containing sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
1
15
0
2
Order By: Relevance
“…A food that resulted in a slower release of energy could eliminate the potential for hypoglycemia after ingestion of a quickly digesting food. Previous research has shown that ingesting a more complex carbohydrate with a slower release of available carbohydrate results in a higher blood glucose concentration during exercise than more quickly digesting starches [2,17,18]. This higher blood glucose concentration throughout exercise can result in a longer, enhanced performance during exercise [19].…”
Section: Discussionmentioning
confidence: 99%
“…A food that resulted in a slower release of energy could eliminate the potential for hypoglycemia after ingestion of a quickly digesting food. Previous research has shown that ingesting a more complex carbohydrate with a slower release of available carbohydrate results in a higher blood glucose concentration during exercise than more quickly digesting starches [2,17,18]. This higher blood glucose concentration throughout exercise can result in a longer, enhanced performance during exercise [19].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Therefore, the starch type may affect parameters of physiological processes and consequently alter the life-span, although information related to this topic is scarce. Some human studies [17][18][19] using cooked meals as starch sources have indicated that rice starch compared to other starches, including corn starch, caused less glucose and insulin response in the blood of humans. Our preliminarily study with gelatinized starches showed that rice starch compared to corn starch significantly lowered the body weight and epididymal adipose tissue weight in ddY mice (unpublished observation, Yamaki et al).…”
Section: Resultsmentioning
confidence: 99%
“…La seconde raison est que les glucides exogènes, notamment le glucose et ses polymères, ont des effets ergogènes au cours de l'exercice prolongé . Burelle et al, 2006Burelle et al, , 1997Decombaz et al, 1985;Guezennec et al, 1989;Jandrain et al, 1993;Massicotte et al, 1994Massicotte et al, , 1986Massicotte et al, , 1989Massicotte et al, , 1990Slama et al, 1989), galactose (Burelle et al, 2006;Leijssen et al, 1995), saccharose Leese et al, 1996;Massicotte et al, 1996a), maltose (Hawley et al, 1992b), polymères de glucose (Guezennec et al, 1993(Guezennec et al, , 1989Jarvis et al, 1992;Johannsen et Sharp, 2007;Leese et al, 1996;Massicotte et al, 1989;Rehrer et al, 1992), triacylglycérols à chaîne moyenne (MCT) Satabin et al, 1987), ou à longue chaîne (LCT) (Satabin et al, 1987)], ou de mélanges de substrats exogènes [glucose + fructose Hulston et al, 2009;Jentjens et al, 2004b;Jeukendrup et al, 2006;Massicotte et al, 1996a;Riddell et al, 2001), glucose + saccharose (Jentjens et al, 2004c, glucose + fructose + saccharose (Jentjens et al, 2004a(Jentjens et al, , 2006, glucose + maltose (Jentjens et al, 2004c), glucose + lactate (Péronnet et al, 1997), glucose + MCT (Goedecke et al, 1999b;...…”
Section: Vue D'ensemble Des éTudesunclassified
“…Ceci tient principalement à deux raisons. La première est que les méthodes de traçage nécessaires pour décrire l'oxydation des substrats exogènes sont beaucoup moins invasives (voire non-invasives) que celles qui sont nécessaires pour décrire de façon dé-taillée la sélection des substrats endogènes : glycogène musculaire (Decombaz et al, 1985;Timmons et al, 2007b) et glucose du plasma (Bosch et al, , 1996b Hawley et al, 1994a,b) ; glucose circulant provenant du glycogène hépatique (Bosch et al, , 1996bHawley et al, 1994a;Jeukendrup et al, 1999b; Burelle et al, 2006Burelle et al, , 1997Decombaz et al, 1985;Guezennec et al, 1989;Jandrain et al, 1993;Massicotte et al, 1994Massicotte et al, , 1986Massicotte et al, , 1989Massicotte et al, , 1990Slama et al, 1989), galactose (Burelle et al, 2006;Leijssen et al, 1995), saccharose Leese et al, 1996;Massicotte et al, 1996a), maltose (Hawley et al, 1992b), polymères de glucose (Guezennec et al, 1993(Guezennec et al, , 1989Jarvis et al, 1992;Johannsen et Sharp, 2007;Leese et al, 1996;Massicotte et al, 1989;Rehrer et al, 1992), triacylglycérols à chaîne moyenne (MCT) Satabin et al, 1987), ou à longue trials with glucose ingestion (expts I and II), according to the procedure of Mosora et al (20), using Eq. 7 and taking the observed R value of expired COZ: 1) at rest or 2) during exercise with water ingestion as reference.…”
unclassified